Development of an Indoor Experimental Environment for Cooperative Navigation Using UWB-Based Positioning for Research and Education - Cunha, Rafael Xavier Silva; Ramos, Daniel Costa (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2025)
The integration of technological advancements in engineering education faces challenges in providing interactive, safe, and practical learning environments. Cooperative robotics, particularly involving of Unmanned Aerial Vehicle (UAV), presents significant opportunities for enhancing academic engagement by facilitating hands-on experimentation and active learning methodologies. However, traditional indoor positioning systems, such as GPS, are inadequate for controlled laboratory settings. This paper proposes an integrated approach that combines a real-world laboratory environment with a simulation framework to enhance cooperative robotics education. The system utilizes Ultra-Wideband (UWB) technology for precise indoor positioning, enabling collaborative navigation between aerial and terrestrial robots. A key contribution of this study is the development and implementation of a dual-environment setup, comprising a physical testbed and a Webots-based simulation, allowing students and researchers to conduct safe and scalable experiments before real-world deployment. Experimental validation demonstrated the effectiveness of the proposed approach by comparing the trajectory accuracy of UAV and rovers in both simulated and physical settings. The results confirm that the system offers a reliable platform for robotics education, with trajectory execution error below 0.4 m and consistent synchronization between simulation and real-world tests, enabling students to develop practical skills in autonomous navigation, positioning technologies, and robotic collaboration. Furthermore, this integrated approach facilitates progressive learning by enabling the application of concepts from basic to advanced levels within the simulation before real-world implementation, supporting continuous educational development in emerging technologies. This work highlights the importance of integrating simulation with real-world testing to foster an effective learning environment in engineering education.